Dynamics of Self-Regulation: A Study of College Students Who Occupy Dual Roles as Couples and Young Academics - Riski, Dea; Rosyidi, Hamim Rosyidi; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2025)
Self-regulation is an individual's ability to plan, control, and reflect on thoughts, emotions, and behaviors in order to achieve desired goals. College students who marry while still studying face unique challenges in the form of dual roles: student and spouse. This situation demands strong self-regulation skills to maintain balance between the two. This study aims to explore the dynamics of self-regulation in married seventh-semester college students. This study used a qualitative approach with phenomenological methods to explore the participants' subjective experiences. Data were collected through in-depth interviews and direct observation of two married seventh-semester female college students. Analysis was conducted thematically, emphasizing the interpretation of the meaning of the participants' experiences. The results showed that both participants were able to apply self-regulation through time management aligned with their daily schedules, active communication with their partners, and setting academic and family priorities. Motivation to study was driven by personal responsibility, promises to family, and emotional support from their partners. Despite facing the pressures of dual roles, both participants demonstrated different adaptation strategies, both structured and flexible, to maintain academic and family balance. This study confirms that self-regulation, social support, and personal discipline are important factors for the academic success of married college students. Keywords: self-regulation, married students, dual roles